PELAKSANAAN TUGAS DAN WEWENANG HAKIM PENGAWAS DAN PENGAMAT PENGADILAN NEGERI DENPASAR DALAM PEMBINAAN NARAPIDANA - I Dewa Made Suartha (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2014)
How is the implementation of duties and authorities of supervisors andobservers judges of Denpasar District Court in founding the convict? What areobstacles that occur in implementation of duties and authorities of supervisorsand observers judges of Denpasar District Court in founding the convict? The method used in this research was empirical legal research. Itscharacteristic is descriptive.  The data sources that used are primary data,secondary data and tertiary data. The primary data / field data were obtained byinterviewing the relevant law enforcement officer that has been determined as asample. The secondary data were obtained of literature studies. The data wasanalyzed by qualitative descriptive analysis to get the vivid conclusion anddescription in discussing the problems in this research. Conclusions derived from this study include: implementation of duties andauthorities of supervisors and observers judges of Denpasar District Court infounding the convict are not running optimally in accordance with the legislationin force. The factor that obstruct are the numbers of supervisors and observersjudges of Denpasar District Court were not adequate, that was one person, therewas no special fund (Operational fund) and there were no strict sanctions forthose when they could not do the duties according to the applicable law; theycould only appeal to the law enforcement agencies / officers of Class IIADenpasar Penitentiary founding the convict.